Relapse-Free Survival as a Surrogate for Overall Survival in the Evaluation of Stage II–III Melanoma Adjuvant Therapy. (22nd August 2017) - Suciu, Stefan; Eggermont, Alexander M. M.; Lorigan, Paul; Kirkwood, John M.; Markovic, Svetomir N.; Garbe, Claus; Cameron, David; Kotapati, Srividya; Chen, Tai-Tsang; Wheatley, Keith; Ives, Natalie; de Schaetzen, Gaetan; et al.
Abstract: Background: We assessed whether relapse-free survival (RFS; time until recurrence/death) is a valid surrogate for overall survival (OS) among resected stage II–III melanoma patients through a meta-analysis of randomized controlled trials. Methods: Individual patient data (IPD) on RFS and OS were collected from 5826 patients enrolled in 11 randomized adjuvant trials comparing interferon (IFN) to observation. In addition, IPD from two studies comparing IFN and vaccination in 989 patients were included. A two-level modeling approach was used for assessing Spearman's patient-level correlation ( rho ) of RFS and OS and the trial-level coefficient of determination ( R² ) of the treatment effects on RFS and on OS. The results were validated externally in 13 adjuvant studies without available IPD. We then tested the results on the European Organisation for Research and Treatment of Cancer (EORTC) 18071 double-blind trial comparing ipilimumab 10 mg/kg with placebo, which showed a statistically significant impact of the checkpoint inhibitor on RFS and OS. All statistical tests were two-sided. Results: With a median follow-up of seven years, 12 of 13 trials showed a consistency between the IFN vs No IFN differences regarding RFS (hazard ratio [HR]RFS = 0.88) and OS (HROS = 0.91), but the small trial, Eastern Cooperative Oncology Group 2696, was an outlier (HRRFS = 0.72 vs HROS = 1.11). Therefore, even if rho was high, R² was low and could not reliably be estimated. Based on the 12 trials, rho remained high (0.89), and the hazard ratios for RFS and OS were strongly correlated ( R² = 0.91). The surrogate threshold effect for RFS was estimated to be 0.77. For the EORTC 18071 trial, the hazard ratio for RFS was 0.75, predicting an effect of ipilimumab on OS. This was subsequently confirmed (HROS = 0.72, 95.1% confidence interval = 0.58 to 0.88, P = .001). Conclusions: In high-risk stage II–III melanoma, RFS appeared to be a valid surrogate end point for OS for adjuvant randomized studies assessing interferon or a checkpoint inhibitor. In future similar adjuvant studies, a hazard ratio for RFS of 0.77 or less would predict a treatment impact on OS.